2020
DOI: 10.3390/polym12112674
|View full text |Cite
|
Sign up to set email alerts
|

Development of Laser Drilling Strategy for Thick Carbon Fibre Reinforced Polymer Composites (CFRP)

Abstract: Composites from carbon fibre reinforced polymers (CFRPs) play a significant role in modern manufacturing. They are typically used in aerospace and other industries that require high strength-to-weight ratios. Composite machining, however, remains a challenging job and sometimes is hampered by poor efficiency. Despite considerable research being conducted over the past few years on the machining of composite materials, the material nevertheless suffers from delamination, fibre loss, and imperfect finishing of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(13 citation statements)
references
References 20 publications
1
11
0
Order By: Relevance
“…Figure 3 a,b show that the ablation depth and HAZ of CFRP were reduced as the rotational speed of the laser increased, while both increased for higher power. As the rotational speed of the laser increased, the number of laser pulses per unit area upon on the material decreased, which led to the ablation depth and HAZ decreases, a result that is consistent with previous studies [ 18 , 22 ]. It is worth noting that in Figure 3 a, the ablation depth corresponding to the laser power of 0.7 W to 2.08 W does not change significantly with the increase of rotational speed of laser between 600 rpm to 1800 rpm.…”
Section: Resultssupporting
confidence: 91%
See 2 more Smart Citations
“…Figure 3 a,b show that the ablation depth and HAZ of CFRP were reduced as the rotational speed of the laser increased, while both increased for higher power. As the rotational speed of the laser increased, the number of laser pulses per unit area upon on the material decreased, which led to the ablation depth and HAZ decreases, a result that is consistent with previous studies [ 18 , 22 ]. It is worth noting that in Figure 3 a, the ablation depth corresponding to the laser power of 0.7 W to 2.08 W does not change significantly with the increase of rotational speed of laser between 600 rpm to 1800 rpm.…”
Section: Resultssupporting
confidence: 91%
“…In addition to the above, it is worth noting that the depth variation of auger drilling was not uniform. The spiral drilling apparatus in this study rotated at a certain speed leading the rotating beam to form a spiral track at the same angular speed, which is different from a previous study in which a galvanometer was used to drill at an equal linear speed [ 13 , 18 , 19 ]. Therefore, the cross-section profile of the hole formed by the device in the drilling process was also different from that of drilling with a galvanometer.…”
Section: Resultsmentioning
confidence: 97%
See 1 more Smart Citation
“…A variety of studies have been reported that have investigated the laser beam-induced machining of CFRP composites. Various experimental parameters regarding laser machining systems, including laser wavelength, pulse duration, repetition rate, beam size, scan speed, beam overlap, and power density, have been systematically examined with simulation analyses [17][18][19][20][21][22][23][24][25][26][27][28]. A previous study has found that the green wavelength has advantages regarding control of ablation depth due to shorter absorption length and lower ablation threshold fluence for carbon, compared to the infrared wavelength [17].…”
Section: Introductionmentioning
confidence: 99%
“…Traditional material composites with enhanced mechanical properties by adding carbon fiber are also reported. The latest advanced technology in cutting and drilling by using a fiber laser is also reported and discussed in the article of Ahmad Sobri et al [ 2 ]. They also reported another interesting article on the effect of the machining input condition, especially the presence of entry and exit holes on the delamination of the composite layers [ 3 ].…”
mentioning
confidence: 99%